(untitled) (Sevana: Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of information technology encourages companies to utilize application systems to support the management of accounting data effectively and efficiently. PT. Jawa Taiko Mineralindo, as a company that owns various types of fixed assets, requires an accurate and structured depreciation calculation system. The problem faced is that the depreciation calculation process for fixed assets is still done manually, which has the potential to cause calculation errors and delays in report presentation. Therefore, this project aims to implement an application for calculating fixed asset depreciation using the double declining balance method based on Microsoft Access. The methods used in this project include data collection through observation, interviews, and literature review, as well as system design using Microsoft Access as the database and information processing tool. The result of this project is an application capable of automatically calculating fixed asset depreciation, storing asset data in an integrated manner, and generating faster and more accurate depreciation reports. By implementing this application, it is expected that PT. Jawa Taiko Mineralindo can improve the efficiency of fixed asset management and minimize errors in the depreciation calculation process.